Democracy's children?: the constitution of male subjectivity of coloured adolescents awaiting trial in post-apartheid Cape Town - Cooper, Adam (Department of Psychology, 2024)
Th is resl..'.an.:h project is an eploration into the Ii es of 25 or· democracy· s chi ldrl..'.n ·. Arrikaans speaking. coloured adolescents ,rnaiting trial. all of \hom .'.Orne from powrty-strickcn. violent areas on the Cape Flats. These boys li e in ah istorical context \ here the new South African dcmucrac: has not (yet) de Ii ered benefits for all of its ·chi ldre11°. This is the contet in which I am eploring their di ided. ambialent and paradoical masculinities. These :oungsters \CIT intenie\cd indh iduall::, and in fixus groups. at a centre called Horizons. near Cape Tcm n. The author eamines ho\ the,,e boys constitute their fragile sub_iecthitics through multiple. contradictory discourses or masculinit:, and hO\ the: in,est in these discourses in attempts partial I:, to allcviak the multiple anieties they npericnce in their Ii Yes. The hO s inserted themscles \ ithin three main discomses of masculinitY. . . H:, per-masculinit:, \as constructed through violent gang acti ity and subjugating women. Traditional masculinity involved sentiments or prm ide and protect. exerted in a non- iolent manner. Finally. mythopoetic masculinit:, CL1mprises open emotional epressinn. especial I:, tm,ards their mothers. Although these ho::-s can·t \in.as the material and discursie odds are stacked too heaily against them. thi-, docs not mean the:, arc automaton'>. simpl:, the dupes of fate. I he: exen agency through unique contigurations Llfthcse discourses. temporarily becoming ·1-foll:,,ood heroes· and creating gangster ·brotherhoods· \hich resist the social dislol..'.ation produced b:, their historical situation. To some degree. then. ·democrac:, ·s children· use the ver:, discourses \ hich llXm and I irn it them. to exert agenc:. The author argues that b:, studying these young men as inherently divided and cornple eperiential beings. as \ell as imoluntaril: inserted into the social and material r..:alms. \e can begin to understand their lives in a meaningful ,,a:, and come to terms with the terrifying acts the: commit.